Temporal changes in fish species composition of headwater streams of the upper Paraguay and Paraná basins, Brazil - doi: 10.4025/actascibiolsci.v32i3.6160 - Karina Keyla Tondato; Yzel Rondon Súarez (Acta Scientiarum. Biological Sciences, 2010)
This study was carried out in headwater streams in the Paraguay and Paraná river basins, with bi-monthly samples from January to November 2004, aiming to quantify the influence of environmental factors on the temporal rate of turnover in species composition of the fish communities. The environmental variables explained 73.5% of the variation in beta diversity and 52.5% of the variation in mean dissimilarity. Altitude was the only environmental descriptor that significantly explained the variation in beta diversity and mean dissimilarity in both basins.